The Impacts of Time Access Restrictions and Vehicle Weight Restrictions on Food Retailers and the Environment - Quak, Hans; Koster, René de (European Journal of Transport and Infrastructure Research, 2006)
Urban freight transport has many sustainable aspects. It contributes to economic vitality and the competitiveness of a region. However, the less socially and environmentally friendly effects such as noise, pollutant emissions, and nuisance, are usually the central theme in designing urban freight transport policies. Restricting policies as time access restrictions and vehicle restrictions gain popularity among Dutch local authorities. More than half of the municipalities uses time access restrictions. In spite of the popularity of these policy measures, the effects on the distribution of retailers, the environment and the transport costs are not known yet. In this paper we present three case studies of food retailers, in order to examine the effects of time access restrictions and vehicle weight restrictions. We discuss the impacts on the transport costs and the distribution processes (on the retailer’s side) and the environmental impacts. To find these effects we design five scenarios, in which we vary the length of time access restrictions, the allowed weight of the weight restriction and the number of cities in which these regulations are used. In these scenarios we adapt, based on the likely reaction of the involved food retailers, the distribution activities to fit the regulations. The results show that the vehicle weight restriction as well as the time access restrictions have a negative impact on the retailers’ transport costs. In most cases we see that the policy measures also cause an increase in the pollutant CO2 emissions that are emitted during the distribution of the goods. The time access restrictions cause a cost-increase that develops more or less convexly, as more stores are affected by this policy measure. The turning point is around 45% of the stores affected. The weight restriction causes linear cost-increase as more stores are affected. Both policy measures affect especially the roundtrips that combine multiple less than truckload orders for different stores. The policy measures have a different effect on different retailers.